Probiotic Intervention in Cyprinus carpio Culture: Evaluating Water Quality Dynamics, Fish Health and Sustainable Pond Management - Maindoli, Sandeep Dutt; Bisht, Harish Chandra Singh; Bhandari, Niharika; Bisht, Maanya; Sharma, Netra Pal; Arya, Manoj Kumar; Dewali, Seeta; Bisht, Satpal Singh (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Probiotics are beneficial microorganisms that enhance water quality and improve fish health, offering a sustainable alternative to conventional water treatment methods. This study evaluated the impact of probiotic-enhanced Biofloc technology on the water quality and growth performance of Cyprinus carpio fingerlings. Two treatments were compared: T1 (Biofloc without probiotics) and T2 (Biofloc with probiotics) over eight months. Key water quality parameters, including pH, turbidity, dissolved oxygen (DO), carbon dioxide (CO₂) and ammonia, were monitored. T2 consistently demonstrated slightly improved DO levels and reduced ammonia concentrations compared to T1, suggesting better water quality stability. Growth performance parameters revealed enhancement in T2. The final body weight of fingerlings in T2 reached 15.50 ± 1.1 g compared to 8.20 ± 1.0 g in T1. Specific growth rate (SGR) was substantially higher in T2 (3.70 ± 0.22 %) than in T1 (2.10 ± 0.15 %), and the feed conversion ratio (FCR) improved from 1.45 ± 0.10 in T1 to 0.80 ± 0.06 in T2. The survival rate was also better in the T2 (93 ± 0.9 %) compared to the T1 (90 ± 1.2 %). The findings indicate a strong positive correlation between the application of probiotic biofloc and enhanced water quality, as well as superior growth performance in C. carpio culture.